2001
DOI: 10.1111/0019-8676.00209
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Are the Self‐Employed More Satisfied with Their Work?

Abstract: Analysis confirms that the self-employed are more satisfied with their jobs because their work provides more autonomy, flexibility, and skill utilization and greater job security. These underlying mechanisms have been stable over the last 30 years and are not due simply to personality differences. The self-employed job satisfaction advantage is relatively small or nonexistent among managers and members of the established professions-occupations where organizational workers have relatively high autonomy and ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
303
1
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(343 citation statements)
references
References 24 publications
26
303
1
13
Order By: Relevance
“…For many entrepreneurs, however, it seems to be that money is only part of what matters. They gain utility from greater autonomy, from broader skill utilization, and from the possibility of pursuing their own ideas (Benz, 2005;Benz and Frey, 2004;Hundley, 2001). There is empirical evidence that even after controlling for job and personal characteristics, self-employed individuals tend to be more satisfied with their jobs than paid employees (e.g., Blanchflower, 2000;Frey and Benz, 2003 these non-monetary returns go away (e.g., the entrepreneur finds herself less independent than she had originally assumed), the entrepreneur might be more willing to quit her business and search for new opportunities either in a wage-earning job or as a serial entrepreneur.…”
Section: Necessity Versus Opportunity Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…For many entrepreneurs, however, it seems to be that money is only part of what matters. They gain utility from greater autonomy, from broader skill utilization, and from the possibility of pursuing their own ideas (Benz, 2005;Benz and Frey, 2004;Hundley, 2001). There is empirical evidence that even after controlling for job and personal characteristics, self-employed individuals tend to be more satisfied with their jobs than paid employees (e.g., Blanchflower, 2000;Frey and Benz, 2003 these non-monetary returns go away (e.g., the entrepreneur finds herself less independent than she had originally assumed), the entrepreneur might be more willing to quit her business and search for new opportunities either in a wage-earning job or as a serial entrepreneur.…”
Section: Necessity Versus Opportunity Entrepreneurshipmentioning
confidence: 99%
“…On the other hand, the same argument can also be used to motivate the opposite case. Once the non-monetary returns from entrepreneurship go away, a "richer" business owner can afford to stay away from entrepreneurship (for more on the non-monetary returns of entrepreneurship, see Benz, 2005;Benz and Frey, 2004;Hundley, 2001). In light of these two conflicting arguments, the impact of the entrepreneur's capital endowment on survival in self-employment remains unclear.…”
Section: Other Determinants Of Survival In Self-employmentmentioning
confidence: 99%
“…Prottas (2008) examined whether reported job autonomy provides more value or bene…t to the self-employed than it does to employees. Consistently, selfemployed individuals have been found to report greater job autonomy (Hundley 2001, Thompson et al 1992 and that the desire for greater autonomy was an important motive in their pursuing self-employment (Feldman and Bolino 2000). Also, Hackman and Oldham (1975) suggested that job that provide autonomy are more intrinsically motivating (for most individuals) than those which are not.…”
Section: Introductionmentioning
confidence: 99%
“…Strong investor protection, however, means that the freedom of entrepreneurs to run their own firms is constrained. Such reduced entrepreneurial freedom can severely discourage entrepreneurship, which has important non-pecuniary benefits such as "being one's own boss" (Hamilton 2000, Hundley 2001, and Moskowitz and Vissing-Jørgensen 2002. This potential trade-off raises the central question of our study: How does investor protection affect entrepreneurship and business creation?…”
Section: Introductionmentioning
confidence: 97%